Filling the learning gap in program implementation using participatory monitoring and evaluation: Lessons from farmer field schools in Zanzibar - Zerfu, Elias; Kebede, Sindu W. (International Food Policy Research Institute, 2013)
This study is motivated by the idea that even though participatory monitoring and evaluation (PM&E) is widely accepted as a tool to manage development programs to be effective, its application is widely constrained by its high start-up resource requirements in terms of both finance and time. However, this paper argues that after the initial investment is made, the payback from using PM&E is much higher both in terms of grassroots-level learning, empowerment, and capacity building and in terms of higher-level strategic decision making which enhances impact.